Beyond unequal access: Acculturation, race, and resistance to pharmaceuticalization in the United States - Crystal Adams; Anwesa Chatterjee; Brittany M. Harder; Liza Hayes Mathias (Elsevier, 2018)
Trends toward pharmaceuticalization in Western countries have led to increased research and theorizing about the roles macro-level institutions, structures, and collective actors play in contributing to patients' reliance on prescription drugs. Relatively less work has focused on the degree to which patients resist pharmaceuticalization pressures, and even less research has explored the factors contributing to patients' resistance to pharmaceuticalization. Drawing on focus groups with patients who had been recently prescribed a prescription drug, this paper investigates how marginalization in the mainstream US society, as measured by acculturation and race, contributes to differences in patients' subjective experiences and responses to prescription drugs. We find that racial minorities report a greater skepticism of prescription drugs compared to whites and express that they turn to prescription drugs as a last resort. While highly acculturated participants rarely discuss alternatives to prescription drugs, less acculturated racial minorities indicate a preference for complementary and alternative remedies. We draw on the literatures on the pharmaceuticalization of society and the social nature of medicine to examine the role marginalization plays in patients' views of prescription drugs. Public health research conceives of racial minorities' lower rates of prescription drug usage compared to whites as primarily a problem of lack of access. Our results suggest another piece to the puzzle: minorities resist pharmaceuticalization pressures to express their cultural and racial identities. Keywords: Medical sociology, Prescription drugs, Race, Acculturation